A prática social - viver no mundo da rua - e seus processos educativos - Almeida, Sara Ferreira de (2014)
Due to the inequalities produced by the current socio-economic system that generates the dehumanization of some social groups, such as the street population of Brazil´s cities, it is urgent to consolidate processes of autonomy on the part of this population. This research aims to uncover social practices and educational processes in the consolidated experiences lived by adult women and men that lives on the street, which, every day, fight and resist the marginalization and deprivation of rights reality. The study is guided on theoretical concepts of Critical Social Science and Education as Freedom Practice, taking as central authors Enrique Dussel and Paulo Freire. Adopts as methodological pillars the dialogicity and interaction between researcher and subjects of the research, making use of interviews, participant observation, diary field and round of conversation to collect data. Research shows, from its results, that life on the street is dialectical, multifaceted and complex and cannot be interpreted in a limited way, since there are cases that prove her relentless pursuit of the people To Be More. Data analysis points to the categories: 1) People who are on the street are not garbage that society throws away ", 2)" To live is to learn to live, to inhabit is washing, ironing, cooking "; 3) Living in street is very difficult, but is happy too, you know? "; 4) The street is a world", 5) "on the street I learn a lot, experiences that I will never forget". Involves, therefor, educational processes focused on the production, reproduction and development of human life, showing a street culture. By unveiling the knowledge of this group, as well as the processes of its production, it is expected to contribute to the visualization of diversity in ways of living and resisting of subjects, in opposition to prejudiced stereotypes that fuel discrimination and marginalization of street population in Brazil.